(untitled) (Research, Society and Development, 2020)
This article has as an objective the demonstration of the diversity of intersubjective and integrated approaches, which can be instrumentalized in the school subeject of Geography, through the digital technologies of information and communication - DTIC (Tecnologias digitais da informação e comunicação - TDIC in portuguese). In the first part, we direcionated a reflexion about some of the school challenges and the teaching in nowadays society of the information and knowledge. In a second moment, we presented possibilities of promotion of curricular content of Geography with the help of Google Earth software. In this aim, we performed a socioespacial analysis from the mentioned geotechnology, taking as a referential focus the urban area of the Ceará’s state municipality of Limoeiro do Norte, which is highlighted by its state relevance as a commercial, educational and fruit procuction center of the Jaguaribe River valley region. We based our study on a qualitative approach in a research of bibliographical nature, supporting the investigation in teorists like Imbernón (2010), Coll e Monereo (2010), Evangelista, Moraes e Silva, (2017), Santos (1997, 2006), Corrêa (2010), Japiassu (2006) e Fazenda (1998). The use of the DTICs (TDICs) when well-planned and orientaded by the construction of significant apprenticeships, works as an important ally to the generation and spreading of knowledges at an interrelational, critic, creative and innovative way, connected to the claims of the society and the contemporary youths, which in a long time don’t recognized themselves in the learning methodologies ruled in the pedagogical traditionalism.